2019
DOI: 10.1590/0004-282x20190001
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory markers are beneficial in the early stages of cerebral venous thrombosis

Abstract: Cerebral vein thrombosis (CVT) is a rare but serious cause of acute stroke. Inflammation is a hypothetical etiological factor in CVT. Objective: The aim of this study was to evaluate inflammatory marker levels in CVT patients and compare these with healthy individuals. Methods: This prospective case-control study was conducted with 36 newly-diagnosed CVT patients age- and sex-matched with 40 healthy individuals. The laboratory investigations included a serum hemogram, full biochemistry profiles, high sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 24 publications
0
32
0
1
Order By: Relevance
“…Rashad and Nagai et al [6,33] found intense in ammatory cell in ltration on the infarct area and high level in several in ammation indicators in the early stage of CVT. Also, previous clinical studies have found in ammation indicators (e.g., MPV, RDW, CRP, ESR, and bilirubin) increasing in patients with CVT [8,34,35], potently hinting the correlation between in ammation and the severity and outcome of CVT. Consistent with the previous results, the high levels of WBC, monocyte, neutrophils, and platelets were found in CVT patients compared with the control group.…”
Section: Due To Complex and Nonspeci C Clinical Ndings Of Cvt Delay mentioning
confidence: 76%
“…Rashad and Nagai et al [6,33] found intense in ammatory cell in ltration on the infarct area and high level in several in ammation indicators in the early stage of CVT. Also, previous clinical studies have found in ammation indicators (e.g., MPV, RDW, CRP, ESR, and bilirubin) increasing in patients with CVT [8,34,35], potently hinting the correlation between in ammation and the severity and outcome of CVT. Consistent with the previous results, the high levels of WBC, monocyte, neutrophils, and platelets were found in CVT patients compared with the control group.…”
Section: Due To Complex and Nonspeci C Clinical Ndings Of Cvt Delay mentioning
confidence: 76%
“…For example, in a recent study, researchers suggested that PLR can be used in clinical practices for prediction of no re ow in patients with acute ST-segment elevation myocardial infarction after primary percutaneous intervention [8]. Simultaneously, the study by Tekesin A et al [9] showed a signi cant association between PLR and cerebral vein thrombosis in suspected patients. Another study by Altintas O et al [10] found that, in patients with acute ischemic stroke who underwent endovascular therapy, low-PLR values were shown to be correlated with better clinical outcome (mRS ≤ 2).…”
Section: Discussionmentioning
confidence: 99%
“…Platelet-to-lymphocyte ratio (PLR), as a combination of platelets and lymphocytes, is a new biomarker to re ect the thrombus formation pathway and in ammation pathway. Several pieces of evidence have con rmed that PLR was a potential marker to predict increased in ammation, the risk of myocardial infarction and ischemic stroke [7][8][9][10][11][12]. However, the predictive value of PLR on the outcomes of ischemic stroke with rtPA treatment are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of laboratory evaluation, a complete blood count, coagulation panel, chemistry panel, and inflammatory markers, such as a sedimentation rate and C-reactive protein, should be performed (57). It should be noted that although the use of Ddimer testing has been well established in ruling out the venous thromboembolism, such as pulmonary embolism and deep vein thrombosis, the usefulness of which is still debatable in CVT, with an unacceptable false-negative rate of up to 26%.…”
Section: Cerebral Angiographymentioning
confidence: 99%